(3eYGde GdSffs - (3CHh SdjeGf CMeO Hf EHQGgje GdNWGHi GdHSJis; (3GdSLSJGfj,J (B275 (3g` s ((3MdH s)
(3ChdgG (B:s
(3Chd eG jbQA efg ef HGH eG jbhd EPG ONd GdNdGA s
(3BNQgG (B:s
(3hajg Odjd Ydi LhGR fHT bHhQ GdeTQcjf EPG cGf ajg CQH Ch faY ddeSdejf hCf djSJ MQeJge ai Pdc cMQeI GdeSdejf s
(3QhGjI GdUGFf CHj fUQ eMeO Hf CMeO GdHdNis
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs